An access control for KUKTEM wired LAN AC spot - Ramalingan, Sivaganasan (2006)
Nowadays internet networks has become widespread technology and emerging as one information technology which connects to each other although in a different location or no matter how long as the connection of the network.The are many benefits that internet networks offer not such connecting people around the world or just about business matters but it is also beneficial in studying and learning is the reason why internet networks are so essential in universities environment.The current KUKTEM Wired LAN shows that the network considered not fully secure because there is no authentication mechanism provided.Due to this matter KUKTEM Wired LAN can be accesses by any outsiders or unauthorized parties easily by plug-in the UTP cable direct to face port. Since all users gain access to internet through KUKTEM Wired LAN, due to this the speed of internet connection decreased and network become traffic.So to overcome this kind of problem, the system needs to change to more sophisticated and secure system.Thus,this Wired LAN System (AC-Spot) was developed specifically for KUKTEM users.This system not only control access the internet by users but it become helpful to administrator leT of KUKTEM in order to identify the person,time and IP Addresses of the users who browsing the internet.This Wired LAN System is easy to use because the architecture of the system is user-friendly.This system proved that,it is more efficitmt and secure compare to existing system.Application of this system developed by using PHP(Hypertext Preprocessor),JavaScript,HTML(Hypertext Markup Language)and Microsoft Office Access Generally hoped that,this system become more secure and efficient in KUKTEM internet networks compare to current existing system.